The Effectiveness of Integrated Agribusiness Cooperatives on The Income of Local Farmers - Luh Putu Kirana Pratiwi; I Komang Pranadita Kusuma Jaya; Made Kencana Maharani (Dwijendra University, 2021)
The primary problem is the limited capital owned by the farmers. This study determine agribusiness activities and analyze the effectiveness of the Integrated Agribusiness Cooperative on the income level of farmers in Subak Guama, Tabanan Regency, Bali Province. The research subject is the Subak Guama farmers who receive capital assistance, and the object is the income of farmers. This study used quantitative data with descriptive statistical analysis, namely paired sample t-test. The results showed that: (1) The Subak Guama carries out: integrated rice management activities, rice-livestock integration activities; and task to strengthen household business capital, namely independent business loans; (2) There is a difference in the level of farming income of Subak Guama farmers before and after receiving capital assistance for agribusiness cooperatives of 7.24% with an effective level of 86.69% with effective criteria.